En svensk röst från Kaunas och Vilnius1939–1940: Lennart Kjellbergs brev - Sausverde, Erika (Scandinavistica Vilnensis, 2023)
In this article, I intend to publish a series of letters by Lennart Kjellberg (1913–2004) who had worked as a Swedish lecturer in Lithuania at the University in Kaunas and Vilnius before World War II, in 1939–1940. I met Lennart Kjellberg several times in the early 90s when I, a young scholar after completing Swedish and Nordic studies and a doctorate in historical linguistics, came to Vilnius and started teaching at the University of Vilnius and set up the Department for Scandinavian Studies. We met several times in Uppsala, and Lennart Kjellberg gave me a bundle of copies of his letters, mainly to his bride Ann-Mari Stridbeck written in 1939, encouraging me to publish them. Kjellberg’s letters are an incredibly exciting source of information and insight for those interested in the cultural and political life of Lithuania during that time and in its perception by a young Swedish intellectual. For me, meeting Lennart Kjellberg, besides everything else, was an unexpected collision with the past which had been cut away by Soviet oppression. For those who grew up during the Soviet era, the period before and during the Soviet presence was sort of divided into then and now (before and after World War II). The loss of continuity in Lithuania’s history is perhaps one of its greatest traumas caused by the Soviet period. For this reason, Kjellberg’s letters, most of which are being published here for the first time, not only give us a lively picture of pre-war Lithuania but also contribute to our better understanding of our past and of ourselves.